Chemotherapy, clocks, and the awareness of death: A quantitative phenomenological study - Moskalewicz, Marcin; Kordel, Piotr; Wiertlewska-Bielarz, Jadwiga (Frontiers in Psychology, 2023)
Following a previous phenomenological study of lived time in ovarian cancer, we aimed to find how the frequency of chemotherapy affects patients’ orientation in time and their awareness of mortality. For this purpose, we developed a variation of a front-loaded phenomenological method that combines scientific hypothesis testing with phenomenological insights of both conceptual and qualitative nature. The study is based on a purposive quota sample of 440 patients representative of the Polish cancer population in terms of sex (m:f ratio 1:1) and age (m>65=61%; f>65=53%) and undergoing chemotherapy for at least a month. The exposure environmental factors of interest were temporal: the frequency of chemotherapy [weekly (N=150), biweekly (N=146), and triweekly (N=144)] and time since the beginning of treatment. The study confirmed the relevance of the 'chemo-clock' – patients use the pace of hospital appointments for orientation in time, and significantly more often when in triweekly treatments (weekly 38%; biweekly 61%; triweekly 69.4%; V=0.242, p<.001, while neither age nor time since the beginning of treatment differentiate the usage of calendar categories and the 'chemo-clock'). Simultaneously, chemotherapy increases their awareness of finitude, which again correlates neither with age nor time since the beginning of treatment but is significantly stronger in those with lower chemotherapy frequencies. Lower frequencies of treatment are thus associated with its increased significance, both in terms of its impact on how patients measure time and whether they increasingly consider their mortality.